Cell-free N-glycosylation of peptides using synthetic lipid-linked hybrid and complex N-glycans - Wenzel, Lisa; Hoffmann, Marcus; Rapp, Erdmann; Rexer, Thomas F. T.; Reichl, Udo (Frontiers in Molecular Biosciences, 2023)
Cell-free, chemoenzymatic platforms are emerging technologies towards generating glycoconjugates with defined and homogeneous glycoforms. Recombinant oligosaccharyltransferases can be applied to glycosylate 'empty', i.e. aglycosyalted, peptides and proteins. While bacterial oligosaccharlytransferases have been extensively investigated, only recently a recombinant eukaryotic single-subunit oligosaccharyltransferase has been successfully used to in vitro N-glycosylate peptides. However, its applicability towards synthesizing full-length glycoproteins and utilizing glycans beyond mannose-type glycans for the transfer have not be determined. Here, we show for the first time the synthesis of hybridand complex-type glycans using synthetic lipid carriers as substrates for in vitro Nglycosylation reactions. For this purpose, transmembrane-deleted human β-1,2 Nacetlyglucosamintransferases I and II (MGAT1ΔTM and MGAT2ΔTM) and β-1,4galactosyltransferase (GalTΔTM) have been expressed in E. coli and used to extend an existing multi-enzyme cascade. Both hybrid and agalactosylated complex structures were transferred to the N-glycosylation consensus sequence of peptides (10 amino acids: G-S-D-A-N-Y-T-Y-T-Q) by the recombinant oligosaccharyltransferase STT3A from Trypanosoma brucei.